Self-Adaptive Systems Planning with Model Checking using MAPE-K - da Silva, Aristóteles Esteves Marçal; Andrade, Aline Maria Santos; Andrade, Sandro Santos (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2020: Anais do XXI Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2020.12488, 2020)
This paper presents a model checking-based approach to support the autonomous planning of adaptation actions in Self-Adaptive Systems, designed in consonance with the MAPE-K reference architecture. We evaluated our approach with a case-study aiming at verifying self-healing and self-organizing properties in a distributed and decentralized traffic monitoring system. Results show that our approach is able to generate adaptation plans satisfying the goals for all expected scenarios in such a case-study, providing a flexible formal framework where adaptation strategies and goals can be inserted/removed.